Phospholipase A2 Mediates Apolipoprotein-Independent Uptake of Chylomicron Remnant-Like Particles by Human Macrophages - Mariarosaria Napolitano; Howard S. Kruth; Elena Bravo (International Journal of Vascular Medicine)
Apolipoprotein E-receptor-mediated pathways are the main routes by which macrophages take up chylomicron remnants, but uptake may also be mediated by receptor-independent routes. To investigate these mechanisms, triacylglycerol (TG) accumulation induced by apolipoprotein-free chylomicron remnant-like particles (CRLPw/o) in human monocyte-derived macrophages was evaluated. Macrophage TG content increased about 5-fold after incubation with CRLPw/o, and this effect was not reduced by the inhibition of phagocytosis, macropinocytosis, apolipoprotein E function, or proteoglycan bridging. The role of lipases, including lipoprotein lipase, cholesteryl ester hydrolase, and secretory (sPLA2) and cytosolic phospholipase A2, was studied using [3H]TG-labelled CRLPw/o. Total cell radioactivity after incubation with [3H]TG CRLPw/o was reduced by 15–30% by inhibitors of lipoprotein lipase and cholesteryl ester hydrolase and by about 45% by inhibitors of sPLA2 and cytosolic PLA2 . These results suggest that macrophage lipolytic enzymes mediate the internalization of postprandial TG-rich lipoproteins and that sPLA2 and cytosolic PLA2, play a more important role than extracellular lipoprotein lipase-mediated TG hydrolysis.